PENTAHO SEBAGAI SOLUSI MASALAH PENGOLAHAN DATABASE - Hidayati, Nurtriana (Jurnal Transformatika, 2012)
Information  is the result  of data  processing  plays an important role in anorganization, especially in  decision-making process. Pentaho application of Intelligent Business Products is one of the technologies for collecting, storing, analyzing, and providing access to data to help enterprise users make better business decisions. Pentaho has a function as reporting, analysis, dashboards, data  integration (ETL)  and data  mining.  Pentaho  is better to manage large and complex  data  and be able to  complete the  functional  organization.
Keywords: Pentaho; Database